The properties of complex numbers
Modules\(:|z|\)
We write \( |z| \) the module of a complex number \( z \).
Let be \( (x, y) \in \hspace{0.05em} \mathbb{R}^2, \enspace z \in \mathbb{C}, \enspace \Biggl \{ \begin{gather*}
z = x + iy \\
|z| = \sqrt{x^2 + y^2 } \end{gather*} \)
Modules of the opposite and the conjugate
$$ \forall z \in \mathbb{C}, $$
$$ | z | = | - z | = |\overline{z}| $$
Module of a product
$$ \forall (z, z') \in \mathbb{C}, $$
$$ | z z' | = | z| \hspace{0.2em}. |z' |$$
In the same way, we will have:
$$ \forall z \in \mathbb{C}, \enspace \forall z' \in \mathbb{C^*}, $$
$$ \left| \frac{z}{z'} \right| = \frac{| \ z \ |}{ |z' |} $$
Module of a complex number raised to an integer power
$$ \forall z \in \mathbb{C}, \enspace \forall n \in \mathbb{N}, $$
$$ | z^n | = | z |^n $$
Arguments\(: arg(z) \)
Let be \( (x, y) \in \hspace{0.05em} \mathbb{R}^2, \enspace z \in \mathbb{C}, \)
$$ \Biggl \{ \begin{gather*}
z = x + iy \\
z = |z|.\left(cos(\theta) + isin(\theta) \right) \end{gather*} $$
We write \( arg(z) \) the argument of a cmplex number \( z \).
Arguments of conjugate and opposite
$$ \forall z \in \mathbb{C}, $$
$$ \Biggl \{ \begin{gather*}
arg(\overline{z}) = -arg(z) \\
arg( -z) = \pi + arg(z) \end{gather*} $$
Argument of a product
$$ \forall z, z' \in \hspace{0.05em} \mathbb{C}^2, $$
$$ arg( z z') = arg(z) + arg(z') $$
Argument of an inverse
$$ \forall z \in \mathbb{C^*}, $$
$$ arg\left(\frac{1}{z}\right) = -arg(z) $$
Argument of a quotient
$$ \forall z \in \mathbb{C}, \enspace \forall z' \in \mathbb{C^*},$$
$$ arg\left(\frac{z}{z'}\right) = arg(z) -arg(z') $$
Argument of a complex number raised to an integer power
$$ \forall z \in \mathbb{C}, \enspace \forall n \in \mathbb{Z},$$
$$ arg(z^n) = n . arg(z) $$
Conjugates\(: \overline{z}\)
We write \( \overline{z} \) the conjugate of a complex number \( z \).
Let be \( (x, y) \in \hspace{0.05em} \mathbb{R}^2, \enspace z \in \mathbb{C}, \enspace \Biggl \{ \begin{gather*}
z = x + iy \\
\overline{z} = x -iy \end{gather*} \)
Conjugate of a sum
$$ \forall (z_1, z_2) \in \mathbb{C}, $$
$$ \overline{z_1 + z_2} \hspace{0.2em} = \hspace{0.2em} \overline{z_1} \hspace{0.2em} + \hspace{0.2em} \overline{z_2} $$
In the same way,
$$ \forall (z_1, z_2) \in \mathbb{C}, $$
$$ \overline{z_1 \textcolor{#8E5B5B}{-} z_2} \hspace{0.2em} = \hspace{0.2em} \overline{z_1} \hspace{0.2em} \textcolor{#8E5B5B}{-} \hspace{0.2em} \overline{z_2} $$
Conjugate of a product
$$ \forall (z_1, z_2) \in \mathbb{C}, $$
$$ \overline{z_1 . z_2} \hspace{0.2em} = \hspace{0.2em} \overline{z_1} \hspace{0.2em}. \hspace{0.2em} \overline{z_2} $$
Conjugate of a quotient
$$ \forall z_1 \in \mathbb{C}, \enspace z_2 \in \hspace{0.05em} \mathbb{C}^*, $$
$$ \overline{ \left( z_1 \over z_2 \right)} \hspace{0.2em} = \hspace{0.2em} \frac{\overline{z_1}}{ \overline{z_2}} $$
Complex number multiplied by its conjugate
$$ \forall z \in \mathbb{C}, $$
$$ z \hspace{0.2em} . \overset{-}{z} = x^2 + y^2 $$
Conjugate of a complex number raised to an integer power
$$ \forall z \in \mathbb{C}, \enspace \forall n \in \mathbb{N},$$
$$ \overline{z^n} \hspace{0.2em} = \hspace{0.2em} (\overline{z})^n $$
Recap table of the properties of the complex numbers formulas
Click on the title to access to the recap table.
Demonstrations
Let us write the complex numbers \( |-z|\) et \( | \overline{z} | \) under their algebraic form.
$$ \Biggl \{ \begin{gather*}
|-z| = \sqrt{(-x)^2 + (-y)^2} = \sqrt{x^2 + y^2 } = |z| \\
| \overline{z} | = \sqrt{x' + (-y)^2 } = \sqrt{x^2 + y^2 }= |z| \end{gather*} $$
And finally,
$$ \forall z \in \mathbb{C}, $$
$$ | z | = | - z | = |\overline{z}| $$
Let us write the complex numbers \( z, z' \) under their algebraic form.
$$ \Biggl \{ \begin{gather*}
z = x + iy \\
z' = x' + iy' \end{gather*} $$
Calculating \( z z' \), we do have:
$$ z z' = (x + iy ) (x' + iy' )$$
$$ z z' = (xx' - yy') + i(x y' + x' y) $$
Then, calculating \( | z z' | \):
$$ | z z' | = \sqrt{ (xx' - yy')^2 + (x y' + x' y)^2 } $$
$$ | z z' | = \sqrt{ (xx')^2 -2xx'yy' + (yy')^2 + (x y')^2 +2x y'x' y + (x' y)^2 } $$
$$ | z z' | = \sqrt{ (xx')^2 + (yy')^2 + (x y')^2 + (x' y)^2 } \qquad (1) $$
In the end, calculating \( | z| \hspace{0.2em}. |z' | \) we do have:
$$ | z| \hspace{0.2em}. |z' | = \sqrt{ (x^2 + y^2) }\sqrt{ \left((x')^2 + (y')^2 \right) } $$
$$ | z| \hspace{0.2em}. |z' | = \sqrt{ (x^2 + y^2)\left((x')^2 + (y')^2 \right) } $$
$$ | z| \hspace{0.2em}. |z' | = \sqrt{ x^2(x')^2 + x^2(y')^2 + y^2(x')^2 + y^2(y')^2 } $$
$$ | z| \hspace{0.2em}. |z' | = \sqrt{ (xx')^2 + (yy')^2 + (x y')^2 + (x' y)^2 } \qquad (2) $$
We now notice that both expressions \( (1) \) and \( (2) \) are equals, so:
$$ \forall (z, z') \in \mathbb{C}, $$
$$ | z z' | = | z| \hspace{0.2em}. |z' |$$
In the same way, we will have:
$$ \forall z \in \mathbb{C}, \enspace \forall z' \in \mathbb{C^*}, $$
$$ \left| \frac{z}{z'} \right| = \frac{| \ z \ |}{ |z' |} $$
Let us write the complex number \(z\) under its algebraic form.
$$ z= x + iy $$
Let us no calculate \(z^n\):
$$ z^n= (x + iy)^n $$
Then,
$$ | z^n | = \sqrt{ (x^2 + y^2)^n }= (x^2 + y^2)^{\frac{n}{2}} $$
But,
$$ | z | = \sqrt{x^2 + y^2}$$
$$ | z |^n = \left(\sqrt{x^2 + y^2} \right)^n = (x^2 + y^2)^{\frac{n}{2}} $$
We definitely have,
$$ \forall z \in \mathbb{C}, \enspace \forall n \in \mathbb{N}, $$
$$ | z^n | = | z |^n $$
Let us write the complex number \(z\) under its trigonometric form.
$$ z = |z|.\left(cos(\theta) + isin(\theta) \right) $$
-
For the conjugate \(\overline{z}\)
. Let us write the complex number \( \overline{z} \) under its trigonometric form.
$$\overline{z} = |z|.\left( cos(\theta) - isin(\theta) \right) $$
But,
$$ \Biggl \{ \begin{gather*}
cos(\theta) = cos(-\theta) \\
-sin(\theta) = sin(-\theta) \end{gather*} $$
So,
$$\overline{z} = |z|.\left( cos(-\theta) + isin(-\theta) \right) $$
Hence,
$$ arg(\overline{z}) = -arg(z) $$
-
For the opposite \( -z \)
$$-z = -|z|.\left( cos(\theta) + isin(\theta) \right) $$
$$-z = |z|.\left( -cos(\theta) - isin(\theta) \right) $$
But,
$$ \Biggl \{ \begin{gather*}
-cos(\theta) = cos(\pi + \theta) \\
-sin(\theta) = sin(\pi + \theta) \end{gather*} $$
So,
$$ -z = |z|.\left( cos(\pi + \theta) + isin(\pi + \theta) \right) $$
Hence,
$$ arg(-z) = \pi +arg(z) $$
And as a result,
$$ \forall z \in \mathbb{C}, $$
$$ \Biggl \{ \begin{gather*}
arg(\overline{z}) = -arg(z) \\
arg( -z) = \pi + arg(z) \end{gather*} $$
Let us write the complex numbers \( z, z' \) under their trigonometric form.
$$ \Biggl \{ \begin{gather*}
z = |z|.\left(cos(\theta) + isin(\theta) \right) \\
z' = |z'|.\left(cos(\theta') + isin(\theta') \right) \end{gather*} $$
Performing the product \( z z' \), we do obtain:
$$ z z' = |z|.|z'|\left(cos(\theta) + isin(\theta) \right) \left(cos(\theta') + isin(\theta') \right) $$
So,
$$ z z' = |zz'| \Bigl[ \left(cos(\theta)cos(\theta') -sin(\theta) sin(\theta') \right) + i\left(cos(\theta)sin(\theta') + sin(\theta)cos(\theta') \right) \Bigr] $$
Now, thanks to the trigonometric addition formulas, we know that:
$$ \forall (\alpha, \beta) \in \hspace{0.05em} \mathbb{R}^2, \enspace \Biggl \{ \begin{gather*}
sin(\alpha + \beta) = sin(\alpha) cos(\beta) + sin(\beta) cos(\alpha) \\
cos(\alpha + \beta) = cos(\alpha) cos(\beta) - sin(\alpha) sin(\beta) \end{gather*} $$
So that,
$$ z z' = |zz'| \Bigl[ cos(\theta + \theta') + isin(\theta + \theta') \Bigr] $$
And as a result,
$$ \forall z, z' \in \hspace{0.05em} \mathbb{C}^2, $$
$$ arg( z z') = arg(z) + arg(z') $$
Let \(z \in \hspace{0.05em}\mathbb{C}^*\) be a non-zero complex number.
Let us start fro mthe following equation:
$$ z \times \frac{1}{z} = 1 $$
Then,
$$ arg( z \times \frac{1}{z}) = arg(1) $$
But, we know that the argument of a product is the sum of the product's factors of this product:
$$ \forall z, z' \in \hspace{0.05em} \mathbb{C}^2, $$
$$ arg( z z') = arg(z) + arg(z') $$
So that,
$$ arg(z) + arg\left(\frac{1}{z}\right) = 0 $$
And finally,
$$ \forall z \in \mathbb{C^*}, $$
$$ arg\left(\frac{1}{z}\right) = -arg(z) $$
Let \(z \in \mathbb{C}\) be a complex number and \(z' \in \hspace{0.05em}\mathbb{C}^*\) a non-zero complex number.
Let us write the quotient \(\frac{z}{z'}\) under the form of a product:
$$ \frac{z}{z'} = z \times \frac{1}{z'} $$
But, we know that the argument of a product is the sum of the product's factors of this product:
$$ \forall z, z' \in \hspace{0.05em} \mathbb{C}^2, $$
$$ arg( z z') = arg(z) + arg(z') $$
So that,
$$ arg\left(z \times \frac{1}{z'}\right) = arg(z) + arg\left(\frac{1}{z'}\right) $$
So,
$$ arg\left(z \times \frac{1}{z'}\right) = arg(z) -arg(z') $$
And as a result,
$$ \forall z \in \mathbb{C}, \enspace \forall z' \in \mathbb{C^*},$$
$$ arg\left(\frac{z}{z'}\right) = arg(z) -arg(z') $$
Let us write the complex number \( z \) under its trigonometric form.
$$ z = |z|.\left(cos(\theta) + isin(\theta) \right) $$
-
Calculating the square\(: z^2 \)
$$ z^2 = \Bigl[ |z|.\left(cos(\theta) + isin(\theta) \right) \Bigr]^2 $$
So,
$$ z^2 = |z|^2.\left(cos(\theta) + i.sin(\theta) \right)^2$$
$$ z^2 = |z|^2.\left(cos^2(\theta) + 2i.sin(\theta)cos(\theta) - sin^2(\theta) \right)$$
$$ z^2 = |z|^2.\left(cos^2(\theta) - sin^2(\theta) + 2i.sin(\theta)cos(\theta) \right)$$
Now, thanks to trigonometric duplicaiton formulas, we know that:
$$ \forall \alpha \in \mathbb{R}, \enspace \Biggl \{ \begin{gather*}
sin(2\alpha) = 2 sin(\alpha) cos(\alpha) \\
cos(2\alpha) = cos^2(\alpha) - sin^2(\alpha) \end{gather*} $$
Thus, we identify that:
$$ z^2 = |z|^2.\left(cos(2\theta) + i .sin(2\theta) \right)$$
And,
$$ arg(z^2) = 2 . arg(z) $$
-
Proof by a recurrence
Let us show by a recurrence that:
$$ \forall z \in \mathbb{C}, \enspace \forall n \in \mathbb{Z},$$
$$ arg(z^n) = n . arg(z) \qquad (S_n) $$
-
Calculating the first term
$$ z = |z|.\left(cos(\theta) + isin(\theta) \right) $$
$$ z^0 = |z|^0.\left(cos(0 \times \theta) + isin( 0 \times \theta) \right) $$
$$ 1 = 1 \times ( 1 + 0) $$
Thus, \((S_0)\) is true.
-
Heredity
-
With an exponent \( n \) in the natural numbers set \( (n \in \mathbb{N}) \)
Let \( k \in \mathbb{N} \) be a nutral number.
Let us assume that the statement \((S_k)\) is true for all \( k \), and let us verify if it is also the case for \((S_{k + 1})\).
If it is so, we should obtain as a result that:
$$ arg(z^{k+1}) = (k+1) . arg(z) \qquad (S_{k + 1}) $$
Consequently, let us calculate \(z^{k+1}\):
$$ z^{k+1} = |z|^{k+1}.\left(cos(\theta) + isin(\theta) \right)^{n+1} $$
But, we know that the argument of a product is the sum of the product's factors of this product:
$$ \forall z, z' \in \hspace{0.05em} \mathbb{C}^2, $$
$$ arg( z z') = arg(z) + arg(z') $$
So in our case that,
$$ arg(z^{k+1}) = arg( z . z^k) = arg(z) + arg(z^k) $$
$$ arg(z^{k+1}) = arg(z) + arg(z) + arg(z^{k-1}) $$
And so on until:
$$ arg\left(z^{k+1}\right) = (k+1).arg(z) $$
Thus, \((S_{k + 1})\) is true in the natural numbers set \( \mathbb{N}\).
Let us now proove it backwards.
-
With an exponent \( n \) in the natural integers set \( (n \in \mathbb{Z}) \)
Let \( k \in \mathbb{Z} \) be an integer.
Let us assume that the statement \((S_k)\) is true for all \( k \), and let us verify if it is also the case for \((P_{k - 1})\).
If it is so, we should obtain as a result that:
$$ arg(z^{k-1}) = (k-1) . arg(z) \qquad (P_{k - 1}) $$
Calculating now \(z^{k-1}\), we do have:
$$ z^{k-1} = \frac{z^k}{z} $$
So that,
$$ arg(z^{k-1}) = arg\left( \frac{z^k}{z} \right) = arg(z^k) - arg(z) $$
$$ arg(z^{k-1}) = k.arg(z) - arg(z) $$
$$ arg(z^{k-1}) = (k-1).arg(z) $$
Thus, \((P_{k - 1})\) is true for the integers set \( \mathbb{Z}\).
-
Conclusion
The statement \((S_n)\) is true for its first term \(n_0 = 0\) and it is hereditary from terms to terms for all \(n \in \mathbb{Z}\), increasingly and decreasingly.
Thus, by the recurrence principle, this is true for all \(n \in \mathbb{Z}\).
And finally, as a result we do have,
$$ \forall z \in \mathbb{C}, \enspace \forall n \in \mathbb{Z},$$
$$ arg(z^n) = n . arg(z) $$
Let us write the complex numbers \( z_1, z_2 \) under their algebraic form.
$$ \Biggl \{ \begin{gather*}
z_1 = x_1 + iy_1 \\
z_2 = x_2 + iy_2 \end{gather*} $$
Performing their sum, we do have:
$$ z_1 + z_2 = (x_1 + x_2) + i(y_1 + y_2) $$
Now, applying the conjugate of it:
$$ \overline{z_1 + z_2} \hspace{0.2em} = (x_1 + x_2) - i(y_1 + y_2) $$
$$ \overline{z_1 + z_2} \hspace{0.2em} = \hspace{0.2em} \underbrace{(x_1 - iy_1)} _\text{\( \overset{-}{z_1} \)} \hspace{0.2em} + \hspace{0.2em} \underbrace{(x_2 - iy_2)} _\text{\( \overset{-}{z_2} \)} $$
And finally,
$$ \forall (z_1, z_2) \in \mathbb{C}, $$
$$ \overline{z_1 + z_2} \hspace{0.2em} = \hspace{0.2em} \overline{z_1} \hspace{0.2em} + \hspace{0.2em} \overline{z_2} $$
In the same way,
$$ \overline{z_1 \textcolor{#8E5B5B}{-} z_2} \hspace{0.2em} = \hspace{0.2em} \overline{z_1} \hspace{0.2em} \textcolor{#8E5B5B}{-} \hspace{0.2em} \overline{z_2} $$
Let us write the complex numbers \( z_1, z_2 \) under their algebraic form.
$$ \Biggl \{ \begin{gather*}
z_1 = x_1 + iy_1 \\
z_2 = x_2 + iy_2 \end{gather*} $$
Performing their product, we do have:
$$ z_1 . z_2 = (x_1 + iy_1 ) (x_2 + iy_2 )$$
$$ z_1 . z_2 = (x_1x_2 - y_1y_2) + i(x_1 y_2 + x_2 y_1) $$
Now, applying the conjugate of it:
$$ \overline{z_1 . z_2} \hspace{0.2em} = (x_1x_2 - y_1y_2) - i(x_1 y_2 + x_2 y_1) \qquad (3) $$
Let us now calculate the product \( \overline{z_1}. \overline{z_2} \) separately:
$$ \overline{z_1} \hspace{0.2em}.\hspace{0.2em} \overline{z_2} \hspace{0.2em} = (x_1 - iy_1)(x_2 + iy_2) $$
$$ \overline{z_1} \hspace{0.2em}.\hspace{0.2em} \overline{z_2} \hspace{0.2em} = (x_1x_2 - y_1y_2) - i(x_1 y_2 + x_2 y_1) \qquad (4) $$
After having calculated both expressions \( (3) \) and \( (4) \), we notice that they are equals:
$$ \overline{z_1 \hspace{0.2em}.\hspace{0.2em} z_2} \hspace{0.2em} = \hspace{0.2em} \overline{z_1}. \overline{z_2} \ = (x_1x_2 - y_1y_2) - i(x_1 y_2 + x_2 y_1) $$
As a result we do have,
$$ \forall (z_1, z_2) \in \mathbb{C}, $$
$$ \overline{z_1 . z_2} \hspace{0.2em} = \hspace{0.2em} \overline{z_1} \hspace{0.2em}. \hspace{0.2em} \overline{z_2} $$
Let us write the complex numbers \( z \) and \( \overset{-}{z} \) under their algebraic form.
$$ \Biggl \{ \begin{gather*}
z= x + iy \\
\overset{-}{z} = x - iy \end{gather*} $$
Performing their quotient, we do have:
$$ \frac{ z_1 }{ z_2 } = \frac{ x_1 + iy_1 }{ x_2 + iy_2 }$$
Multiplying both numerator and denominator by the denominator's conjugate,
$$ \frac{ z_1 }{ z_2 } = \frac{ (x_1 + iy_1)(x_2 - iy_2) }{ (x_2 + iy_2)(x_2 - iy_2) }$$
So in our case,
$$ \frac{ z_1 }{ z_2 } = \frac{ (x_1 + iy_1)(x_2 - iy_2) }{ x_2^2 + y_2^2 }$$
Then, developping the numerator,
$$ \frac{ z_1 }{ z_2 } = \frac{ x_1x_2 - i(x_1 y_2) + i(x_2 y_1) + y_1 y_2 }{ x_2^2 + y_2^2 }$$
$$ \frac{ z_1 }{ z_2 } = \frac{ x_1x_2 + y_1 y_2 + i(-x_1 y_2 + x_2 y_1) }{ x_2^2 + y_2^2 }$$
Now, applying the conjugate of it:
$$\overline{ \left( z_1 \over z_2 \right)} \hspace{0.2em} = \frac{ x_1x_2 + y_1 y_2 - i(-x_1 y_2 + x_2 y_1) }{ x_2^2 + y_2^2 }$$
$$\overline{ \left( z_1 \over z_2 \right)} \hspace{0.2em} = \frac{ x_1x_2 + y_1 y_2 + i(x_1 y_2 - x_2 y_1) }{ x_2^2 + y_2^2 } \qquad (5) $$
Let us now calculate the quotient \( \frac{\overline{z_1}}{ \overline{z_2}} \) separately:
$$\hspace{0.2em} \frac{\overline{z_1}}{ \overline{z_2}} = \frac{ x_1 - iy_1 }{ x_2 - iy_2 }$$
In the same way as as above,
$$\hspace{0.2em} \frac{\overline{z_1}}{ \overline{z_2}} = \frac{ (x_1 - iy_1)(x_2 + iy_2) }{ (x_2 - iy_2)(x_2 + iy_2) }$$
$$\hspace{0.2em} \frac{\overline{z_1}}{ \overline{z_2}} = \frac{ x_1x_2 + y_1 y_2 + i(x_1 y_2 - x_2 y_1) }{ x_2^2 + y_2^2 } \qquad (6) $$
After having calculated both expressions \( (5) \) and \( (6) \), we notice that they are equals:
$$\overline{ \left( z_1 \over z_2 \right)} \hspace{0.2em} = \hspace{0.2em} \frac{\overline{z_1}}{ \overline{z_2}} = \frac{ x_1x_2 + y_1 y_2 + i(x_1 y_2 - x_2 y_1) }{ x_2^2 + y_2^2 } $$
And finally,
$$ \forall z_1 \in \mathbb{C}, \enspace z_2 \in \hspace{0.05em} \mathbb{C}^*, $$
$$ \overline{ \left( z_1 \over z_2 \right)} \hspace{0.2em} = \hspace{0.2em} \frac{\overline{z_1}}{ \overline{z_2}} $$
Let us write the complex numbers \( z \) and \( \overset{-}{z} \) under their algebraic form.
$$ \Biggl \{ \begin{gather*}
z= x + iy \\
\overset{-}{z} = x - iy \end{gather*} $$
Let us calculate their product:
$$ z \hspace{0.2em} . \overset{-}{z} = (x + iy)(x - iy) $$
We know from the the third quadratic remarkable identity that:
$$ \forall (a, b) \in \mathbb{R},$$
$$ (a + b)(a - b) = a^2 - b^2 $$
So in our case,
$$ z \hspace{0.2em} . \overset{-}{z} = x^2 - i^2y^2 $$
$$ z \hspace{0.2em} . \overset{-}{z} = x^2 + y^2 $$
And finally,
$$ \forall z \in \mathbb{C}, $$
$$ z \hspace{0.2em} . \overset{-}{z} = x^2 + y^2 $$
Let us write the complex numbers \( z \) under its trigonometric form.
$$ z = |z|.\left(cos(\theta) + i.sin(\theta)\right) $$
Calculating \( z^n \), we do have:
$$ z^n= |z|^n.\left(cos(\theta) + i.sin(\theta)\right)^n $$
But we know from the Moivre's formula that:
$$ \forall \theta \in \mathbb{R}, \enspace \forall n \in \mathbb{N}, $$
$$ \left(cos(\theta) + i.sin(\theta)\right)^n = cos(n\theta) + i.sin(n\theta) $$
Then, we can now write that:
$$ z^n= |z|^n.\left(cos(n\theta) + i.sin(n\theta)\right) $$
Let us now apply the conjugate of it:
$$ \overline{z^n} \hspace{0.2em} = \overline{|z|^n}.\left(cos(n\theta) - i.sin(n\theta)\right) $$
$$ \overline{z^n} \hspace{0.2em} = |z|^n.\left(cos(n\theta) - i.sin(n\theta)\right) \qquad (7) $$
Let us now calculate \( (\overline{z})^n \) seperately, starting from \( \overline{z} \).
$$ \overline{z} \hspace{0.2em} = |z|.\left(cos(\theta) - i.sin(\theta)\right) $$
With the Moivre's formula again, we do have:
$$ (\overline{z})^n \hspace{0.2em} = |z|^n.\left(cos(n\theta) - i.sin(n\theta)\right) \qquad (8) $$
After having calculated both expressions \( (7) \) et \( (8) \), we notice that they are equals:
$$ \overline{z^n} \hspace{0.2em} = (\overline{z})^n = |z|^n.\left(cos(n\theta) - i.sin(n\theta)\right) $$
And as a result,
$$ \forall z \in \mathbb{C}, \enspace \forall n \in \mathbb{N},$$
$$ \overline{z^n} \hspace{0.2em} = \hspace{0.2em} (\overline{z})^n $$